Crime and criminality: a multidisciplinary approach - Taylor, Sandie (Routledge, 2016)
Introduction -- Why is a multidisciplinary approach informative? -- What is crime? -- Defining and examining crime from different perspectives -- Concepts in crime definition influencing crime classification -- Nature-nurture explanations of criminal behaviour -- Biological constraints and evolutionary factors -- Social, learning and developmental approaches to understanding criminality -- Decision-making processes by criminals -- Different types of crime and criminal with a focus on nature, nurture and nature-nurture -- White-collar criminals and their crimes -- Psychopaths and their crimes -- Sex offenders and their crimes -- Female offenders and their crimes -- Delinquents and their crimes -- Prediction of criminal behaviour -- Dangerousness, risk assessment and the mentally and the personality disordered offender -- Offender profiling: serial killers -- Reliability of investigative processes -- Eyewitness testimony and extra-legal defendant characteristics -- Cognitive interview -- Confessions -- Discussion about the function of law, its impact on antisocial behaviour and its origins -- "Big5" legal concepts -- Law drives criminality -- Concluding comments -- Glossary -- References -- Appendix